Foreign Direct Investment and the Effects on Economic Growth: Theory, Empirical Evidence and New results from Case Studies in Malaysia. - TEE, Yiing Yann (2008)
Foreign Direct Investment (FDI) has been heralded as a sustainable way to encourage economic and industrial development. This study will critically analyse this contention through the specific case study of Malaysia. Using both secondary and primary data it is found that there are numerous economic benefits to be gained from FDI but negative effects will also result which call into question the supposed success of FDI in Malaysia, most notably the effect of an over-reliance of FDI in a climate where FDI is beginning to wane is deemed worrying by those working in Malaysia.